Determinants of capital structure of the information technology industry - Nuno Miguel Delicado Teixeira; Jo\~ao Filipe Melo Parreira (The International Journal of Management Science and Information Technology (IJMSIT), 2015)
The access to capital, on adequate maturity and amounts, is one of the major constraints to sustainable development of enterprises. So, this paper aims to study the determinants of capital structure of companies in the portuguese information technology sector, which is one of the most important industries in the exports of high value-added products of the country. To this end, we studied the mainstream research developed over the years where we note that there are numerous theoretical developments, but the diversity of work also led us to verify that the issue is not yet fully savvy among finance researchers. The sample consisted on the major 500 companies of the industry, with reference to the value of turnover, as a criterion. Through multiple linear regression, it was found that the most important variables to explain the capital structure were business risk, size and collateral guarantees, which had a positive relation to the level of debt; and the cost of financing, reputation and profitability, which had a negative relationship with debt. Finally, it was observed that the debt level was higher in companies with a higher commercial activity when compared to firms that have a greater focus on service providing.
Keywords: 650; Determinants of capital structure; information technology sector; trade-off; hierarchical selection; strategic positioning